Electronic Learning Media E-Module Open Source-Based on Planetary Type Starter System for Vocational Students - Setiyawan, Andri; Firdaus, Doni Yusuf; Suwahyo, Suwahyo; Apristia, Lelu Dina; Faksi, Sanli; Iman, Muhammad Syamsuddin Nurul; Abrori, Fadhlan Muchlas; Bautista, Guillermo (Elinvo (Electronics, Informatics, and Vocational Education), 2024)
Post-pandemic COVID-19 learning that is carried out in a hybrid manner experiences problems, one of which is minimal self-learning supplements, which affect students' understanding of the material. This study aims to develop an e-module using Sigil software on planetary-type starter system material. Hopefully, it can support improving students' knowledge of the material. This research uses the Research and Development (RnD) method with the ADDIE model. The results of this product were tested on a limited basis by using a one-group pretest-posttest design in class XI TKRO-A with 30 students. The results showed that the E-module that had been developed received a very decent category from media experts, who scored 89.26%, and from material experts, who scored 95.5%. The e-module developed can increase the understanding of the material with a gain value of 0.64 with a moderate category, and a score of 93.75% from the students' responses showed that the e-module is feasible. The conclusion is that the e-module developed is very feasible to use in independent learning and the learning process at school.